Flexible-Rigid Wheelset Introduced Dynamic Effects due to Wheel Tread Flat. (25th September 2021) - Momhur, Awel; Zhao, Y. X.; Li, Wen-Quan; Sun, Ya-Zhou; Zou, Xiao-Long
Abstract : The widespread faults that occur in railway wheels and can cause a massive dynamic impact are the wheel tread flat. The current work considered changes in vehicle speed or wheel radius deviation and studied the dynamic impact load. The modal technique for the impact evaluation induced by the wheel flat was proposed via the finite element analysis (FEA) software package ANSYS, integrated into a multibody dynamics model of the high-speed train CRH2A (EMU) through SIMPACK. The irregularity track line has developed and depends on the selected simulation data points. Additionally, a statistical approach is designed to analyze the dynamic impact load response and effect and consider different wheel flat lengths and vehicle speeds. The train speed influence on the flat size of the vertical wheel-rail impact response and the statistical approach are discussed based on flexible, rigid wheelsets. The results show that the rigid wheel flat has the highest vertical wheel impact load and is more significant than the flexible wheel flat force. The consequences suggest that the wheelset flexibility can significantly improve vertical acceleration comparably to the rigid wheel flats. In addition, the rendering of the statistical approach shows that the hazard rate, PDF, and CDF influence increase when the flat wheel length increases.